Christian Values for a Just Society: Addressing Discrimination Through Religious Education - Bulan, Susanti Embong; Manik, Novida Dwici Yuanri (Indonesian Journal of Religious, 2024)
Indonesia, with its vast cultural diversity, faces social challenges such as discrimination, often arising from differences in ethnicity, religion, and culture. While this diversity enriches social life, tensions between groups frequently occur, affecting social relations. Christian Religious Education (CRE) plays a crucial role in promoting tolerance and respect for differences, which is expected to help reduce discrimination in Indonesia's pluralistic society. This article aims to explore the contribution of CRE in addressing discrimination by instilling values of justice, love, and appreciation for diversity. The research method used is a descriptive qualitative approach, focusing on literature analysis and theoretical studies related to the role of CRE in a multicultural society. The data selected were carefully chosen to ensure relevance to the topic and were analyzed to form a theoretical foundation supporting the development of this article. The research findings indicate that CRE can serve as a means to foster understanding of pluralism and the importance of tolerance in community life. Through Christian teachings on love and justice, CRE encourages individuals to respect human rights and reject discriminatory attitudes. Moreover, CRE also plays a role in educating society to engage in interfaith and intercultural dialogue, contributing to the creation of an inclusive and just community. The contribution of this article is to provide insights into how Christian religious education can be used to build deep social awareness, appreciate differences, and advocate for justice in Indonesia's plural society. Through the teachings of Christian values, CRE can be an effective tool in creating more inclusive social consciousness, strengthening social cohesion, and combating discrimination.